Human Rights and Private Law : Privacy as Autonomy. - Ziegler, Katja S. (Studies of the OIECL., 2007)
Privacy today is much debated as an individual's right against real or feared intrusions by the state, as exemplified by proposed identity cards and surveillance measures in the United Kingdom. In contrast, invasions of privacy by private individuals or bodies tend to arouse less concern. This book attempts to fill the gap by looking at the horizontal application of human rights after Douglas v Hello, Campbell v MGN and Caroline von Hannover v Germany. It provides a conceptual and theoretical framework and also considers specific particularly sensitive areas of law relating to privacy protecti.